CDMA2000 Past, Present and Future - Saad Zaman Asif (Bulletin of Electrical Engineering and Informatics, 2012)
The article looked into the possible future of 3GPP2s CDMA2000 1X and CDMA2000 1xEV-DO networks. The 3G CDMA2000 family of standards including EV-DO (Evolution Data Optimized) is in the daily use of more than 600 million customers across the globe. During the last few years the development efforts around CDMA2000 had been declined and its importance had been overshadowed by more advanced 3GPP LTE and IEEE WiMAX mobile broadband technologies. Due to these reasons, CDMA2000 operators are looking for alternative migration paths. The article investigated multiple facets for the future of CDMA2000 industry and these aspects were covered both from research and operational perspectives. The article first focused on the short term interoperability challenges to LTE and WiMAX and provided some antidotes for addressing these hurdles. The key challenges that were investigated include spectrum planning, authentication and security, end-to-end QoS (Quality of Service), voice enablement and data service continuity. The investigation revealed that a new QoS mapping mechanism between EV-DO and WiMAX similar to the one shown in the article is required for smooth operation. The analysis further indicated that CSFB (Circuit Switched Fallback) and SVLTE (Simultaneous Voice and LTE) were two techniques which could be used to support CS voice on an LTE/CDMA network; however they had different inter-radio access technology interworking requirements. In the following section performance aspects of both WiMAX and EV-DO were highlighted indicating a deep dip in throughput values once the users switches from WiMAX to EV-DO. The article concluded by discussing the future roadmap of CDMA2000 from 1X Advanced and DO Advanced perspectives. A performance comparison between 1X and 1X Advanced and EV-DO and DO Advanced was also presented.